The Business Case For Diversity And Equity - Ismy Novira (Jurnal Manajemen Bisnis Digital Terkini, 2024)
This research aims to explore and analyze the role of diversity and equality in modern organizations. The research method used is a qualitative approach, by conducting case studies of several different organizations in the private sector. Data was collected through in-depth interviews with senior managers, employees, and through analysis of internal company documents. The results show that diversity in terms of background, gender, and expertise can contribute significantly to innovation and creativity within organizations. Meanwhile, the implementation of equality in organizational policies and practices has a positive impact on employee satisfaction, loyalty, and work productivity. Analysis using VOSviewer showed that key concepts that emerged included inclusiveness, fairness, collaboration and respect for individual uniqueness. Nonetheless, challenges related to conflict management, organizational culture adaptation, and managing change remain a key focus in the implementation of diversity and equality in various organizational contexts. The findings provide a deeper understanding of how organizations can leverage diversity and equality as strategic resources to achieve competitive advantage and sustainable growth in an increasingly complex global marketplace.